Fibrinogen Recovery in Fibrinolytic Dogs - Dulock, M. A; Kolmen, S. N (Thrombosis and Haemostasis, 1970)
Hypoprothrombinemic dogs with or without a superimposed hypofibrinogenemia were allowed to recover spontaneously or under the influence of vitamin K. The hypoprothrombinemic status was corrected more rapidly in K-treated animals irrespective of the fibrinogenemic status.Hypofibrinogenemic dogs, irrespective of supplemental vitamin K, showed a biphasic rate of recovery. The initial phase was accelerated when vitamin K was administered, the second phase was not altered by vitamin therapy.It is suggested that vitamin K influence fibrinogen recovery in a manner analogous to its influence on prothrombin recovery; namely, “finalization” of precursor protein and accelerated release of the protein into the circulating fluid compartments.